'The planet that rules our destiny': Alternative development and environmental power in occupied Afghanistan. (April 2017) - Attewell, Wesley
In this article, I explore the role that the United States Agency for International Development and its implementing partners played in the 'alternative development' effort to provide Afghan farmers with sustainable and economically viable alternatives to growing poppy. I argue that alternative development programs in occupied Afghanistan sought to wean farmers off of poppies by creating a rural 'environment' conducive to the cultivation of legal alternative crops. My argument proceeds in four steps. First, I theorize alternative development as a form of 'environmental power'. Second, I put this theoretical framework to work in eastern Afghanistan through a close reading of one of the United States Agency for International Development's flagship alternative development projects: Development Alternative Inc.'s 'Incentives Driving Economic Alternatives – North, East and West'. As Incentives Driving Economic Alternatives: North, East and West (IDEA-NEW) ran its course, its end-state goal shifted from improving production to promoting market exchange. Third, I suggest that IDEA-NEW's marketization efforts produced differentiated subjects of rule, exacerbating already existing patterns of uneven development in the process. Finally, although IDEA-NEW is represented as productive, humanitarian and therapeutic, I conclude by reflecting on how it is undergirded by – and also provides a legitimating armature for – techniques of population management that are destructive of life.